Nitrogen and potassium in the intensitY of Bacterial Blight of coffee seedlings in nutrient solution - Pérez, Cristian David Plaza; Pozza, Edson Ampélio; Pozza, Adélia Aziz Alexandre; Freitas, Aurivan Soares; Silva, Marília Goulart (Coffee Science - ISSN 1984-3909, 2017)
A balanced nutrition can aid in the control of the coffee diseases. Thus, the objective was to evaluate the effect of nitrogen and potassium fertilization in a growth chamber in assessing the intensity of bacterial blight. We used the susceptible cultivar Mundo Novo 376/4. The treatments consisted of five doses of N (3, 7, 11, 15 and 19 mmol L-1) combined with five doses of K (3, 5, 7, 9 and 11 mmol L-1) in a factorial 5 x 5, a total of 25 treatments and three replicates composed of two seedlings. The experimental design was completely randomized. The incidence and severity was assessment. Then, the area under disease progress curve of incidence (AUDPCI) and severity (AUDPCS) were calculated. There was a higher incidence of the disease (97.2%) in the combination of larger doses of N and K. There was a significant difference only for N in AUDPCS, dry mass of plant and chlorophyll a, b and total. The lower AUDPCS (7.79) was obtained with the dose 13.34 mmol L-1 N. There was a significant positive correlation to chlorophyll a, b and total with N and AUDPCS.